Greater willingness to reduce microplastics consumption in Mexico than in Spain supports the importance of legislation on the use of plastics - Garcia-Vazquez, Eva; Garcia-Ael, Cristina; Mesa, Maritza Librada Caceres; Rodriguez, Noemi; Dopico, Eduardo (Frontiers in Psychology, 2023)
Microplastics (MP) threaten all organisms worldwide. MP are produced directly as microbeads in cosmetics and hygiene products, or indirectly from breakage of larger plastics. The control of MP needs consumers’ engagement to refuse products containing microbeads. We conducted a survey with 572 university students from Mexico and Spain, two countries where microbeads are not banned yet. More strict laws for plastic control are enforced in Mexico than in Spain. Results showed that controlling for age and education, despite knowing less about MP, Mexicans checked microbeads from product labels more frequently than Spaniards, and wanted to reduce MP consumption more. A stronger correlation between individual awareness and willingness of MP control was found for Mexican than for Spanish students. Perhaps more strict legislation against plastics creates an environment favorable to MP control. Unclear statement of microbeads on labels was the main reason for not checking microbead contents; environmental education and a stricter control of plastics and MP were identified as necessary policy changes in the two countries. Corporation engagement on clearer product labeling is also suggested.